Wage Subsidy as an Effective Form of Incentive for Employers Who Employs Persons with Disability to Create an Inclusive Labour Market - Hilmi Ardani Nasution (Future Science, 2023)
The government is mandated by disability legislation to ensure the employment rights of individuals with disabilities. To expedite the realization of these employment rights, the government must enact policies that facilitate the integration of disabled individuals into the labor market, one such approach being the provision of incentives to employers. These incentives aim to encourage the hiring of persons with disabilities and one viable option is wage subsidies. This research aims to investigate whether wage subsidies represent the most effective strategy for expediting the fulfillment of employment rights for individuals with disabilities. This study employs a qualitative approach, conducting a literature review based on legal regulations and relevant scholarly literature. The study concludes that wage sub-sidies indeed serve as a valuable mechanism to incentivize entrepreneurs' employers to hire disabled workers, as they allow for the implementation of programs that do not unduly burden employers while promoting the employment of individuals with disabilities.